The catalytic effects of DFI investment - gender equality, climate action and the harmonisation of impact standards: An essay series - Samantha Attridge (Overseas Development Institute (ODI), 2021)
Private investment and a robust private sector are fundamental drivers of economic growth and job creation, which are key ingredients to help tackle poverty. Development finance institutions (DFIs), with their core mandates to promote economic growth through their financing, risk sharing and supporting activities, have been assigned a key role in supporting the achievement of the Sustainable Development Goals (SDGs) and the implementation of the United Nations Framework Convention on Climate Change (UNFCCC) Paris Agreement. This step into the limelight has been accompanied by greater scrutiny of DFI strategies and operational issues, including an increased demand by shareholders and other stakeholders to better understand the impact of DFI investment on the SDGs and the Paris Agreement, as well as for greater accountability and transparency on how this impact is achieved. This essay series focuses on the three themes of the 2021 European Development Finance Institutions (EDFI) impact conference, which was held in May 2021: 1. The catalytic effects of gender-smart investing (Sustainable Development Goal 5), 2. Climate finance impact and related developmental concerns (Sustainable Development Goal 13), 3. The harmonisation of impact management and reporting. - This rich set of essays brings together a wide range of perspectives from academics, researchers and practitioners and covers reviews of impact in these areas, as well as methodological issues which can advance our thinking and understanding in these areas.
Keywords: 330; Climate finance; Climate change; Development finance; Women’ s economic empowerment; Development banks